1991
DOI: 10.1037/0096-1523.17.2.422
|View full text |Cite
|
Sign up to set email alerts
|

Repetition blindness depends on perceptual capture and token individuation failure.

Abstract: A visual prime succeeded by a brief target produces a paradox. Namely, target repetition yields poorer identification accuracy and shorter duration judgments than unrelated prime-target pairs. Experiment 1 manipulated stimulus onset asynchrony to learn when repetition blindness is maximized. Experiments 2 and 3 manipulated expectancy of repetitions through changes in the proportion of repeated trials and instructions, respectively. Results indicate that repetition blindness is influenced by subject strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
3

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 22 publications
7
69
3
Order By: Relevance
“…In addition, the inhibitory effects did not appear to be due to any guessing effects in the three-eld technique. For instance, it has been argued that subjects may be reluctant to say a related target word, especially in the case of the identical condition (see Hochhaus & Marohn, 1991;Park & Kanwisher, 1994). However, that possibility cannot be applied to the present experiment, since all priming conditions were interleaved in the same experiment but only one of them yielded signi cant effects (see Park & Kanwisher, 1994, for a similar argument).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In addition, the inhibitory effects did not appear to be due to any guessing effects in the three-eld technique. For instance, it has been argued that subjects may be reluctant to say a related target word, especially in the case of the identical condition (see Hochhaus & Marohn, 1991;Park & Kanwisher, 1994). However, that possibility cannot be applied to the present experiment, since all priming conditions were interleaved in the same experiment but only one of them yielded signi cant effects (see Park & Kanwisher, 1994, for a similar argument).…”
Section: Resultsmentioning
confidence: 53%
“…Speci cally, the technique used in the study is the three-eld technique (Humphreys, Besner, & Quinlan, 1988), in which a clearly visible prime (in lower-case letters) is followed by a brie y presented upper-case word which is immediately masked, and the percentage of correct target identi cations is measured. With this technique, when the prime and the target are identical, the magnitude of the inhibition effect relative to an unrelated word condition is rather robust (see Hochhaus & Marohn, 1991;Humphreys et al, 1988;Park & Kanwisher, 1994;Perea, 1993;Perea & Gotor, 1994), which has been considered to be a variety of the repetition blindness effect (Bavelier, Prasada & Segui, 1994;Hochhaus & Marohn, 1991;Park & Kanwisher, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have failed to replicate Kanwisher's (1987) findings and have shown, instead, that RB is relatively equivalent whether participants report all items or only the final one (Hochhaus & Marohn, 1991;Kanwisher & Potter, 1990;Luo & Caramazza, 1995). There are also conceptual problems with Kanwisher's (1987) claim that the type refractoriness hypothesis cannot accommodate facilitatory repetition effects in the final-word report task.…”
Section: Memory and Reconstruction Accounts Of Rbmentioning
confidence: 85%
“…For example, for the sentence, "She ate salad andfish even though the fish was raw," readers show poor recall of the second presentation of the word fish relative to recall performance for the following control: "She ate salad and seafood even though thefish was raw." The effect occurs in the repeated case even though the omission of the second word makes the sentence ungrammatical.RB is a robust finding and has been reported now by a number of researchers using a variety of different paradigms (e.g., Hochhaus & Marohn, 1991;Humphreys, Besner, & Quinlan, 1988;Mozer, 1989). The RB effect has been found when both words differ in case (Kanwisher, 1987;Marohn & Hochhaus, 1988) and with as many as three intervening words present between the first and the second repetition.…”
mentioning
confidence: 81%
“…RB is a robust finding and has been reported now by a number of researchers using a variety of different paradigms (e.g., Hochhaus & Marohn, 1991;Humphreys, Besner, & Quinlan, 1988;Mozer, 1989). The RB effect has been found when both words differ in case (Kanwisher, 1987;Marohn & Hochhaus, 1988) and with as many as three intervening words present between the first and the second repetition.…”
mentioning
confidence: 81%